Psychchologism, naturalism and nihilism (A phenomenological critique) - Jonkus, Dalius (Religija ir kultūra, 2006)
The article discusses Husserl’s criticism of Psychologism and the relationship that have with the contemporary crisis of values. In Logical Investigation Husserl criticize not only a psychological foundation of science, but he expresses his preoccupation about rationality in general. Rationality according to Husserl is connected with ethical and political questions. Aron Gurwitsch research shows the existing connection between naturalistic psychology and nihilism. Naturalistic psychology induces a nihilistic conception of human being: human as a biological functions mechanism. This point of view cause a totalitarian tendency in social life and politic.
Keywords: phenomenology; psychologism; naturalism; nihilism